2008
DOI: 10.3852/08-001r
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the gemmae of Papulaspora sepedonioides are neotenous perithecia in the Melanosporales

Abstract: Papulaspora sepedonioides produces large multicellular gemmae with several, thick-walled central cells enclosed within a sheath of smaller thin-walled cells. Phylogenetic analysis of the large subunit rDNA indicates P. sepedonioides has affinities to the Melanosporales (Hypocreomycetidae). The development of gemmae in P. sepedonioides was characterized by light and scanning and transmission electron microscopy and was similar to previous ontogenetic studies of ascoma development in the Melanosporales. However … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…In our phylogenetic study Papulasporasepedonioides , the type species of the genus, was nested in the Microthecium clade, and therefore transferred to this genus. The relationship of this species with the Melanosporales had already previously been demonstrated by Davey et al (2008) and Li et al (2016). However, it has been demonstrated that Papulaspora is a polyphyletic genus, and other species of the genus have been reported as belonging to the classes Leotiomycetes and Sordariomycetes (Ascomycota).…”
Section: Discussionmentioning
confidence: 59%
“…In our phylogenetic study Papulasporasepedonioides , the type species of the genus, was nested in the Microthecium clade, and therefore transferred to this genus. The relationship of this species with the Melanosporales had already previously been demonstrated by Davey et al (2008) and Li et al (2016). However, it has been demonstrated that Papulaspora is a polyphyletic genus, and other species of the genus have been reported as belonging to the classes Leotiomycetes and Sordariomycetes (Ascomycota).…”
Section: Discussionmentioning
confidence: 59%
“…Instead, clusters of thick-walled, dark pigmented cells were present. It is unclear whether these structures represented immature perithecia (Davey et al 2008). In the framework of singular nomenclature for fungi (Taylor 2011), the species are here nevertheless described in sexual genera on the basis of their phylogenetic position within the Chaetomiaceae.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of bulbils or papulospores is non-specific and polyphyletic, as similar compact masses of cells can be produced by a wide range of fungi from different genera and orders (Hotson 1917). The generic type species Papulaspora sepedonioides is a member of the order Melanosporales (Davey et al 2008), but further papulaspora-like asexual morphs have been assigned to Ceratostoma and Chaetomium in the order Sordariales (Bainier 1907;Hotson 1917;Weresub and LeClair 1971;Zang et al 2004). Isolates previously misidentified as P. sepedonioides are currently listed as non-sporulating Chaetomium species (Vinod Mootha et al 2012).…”
Section: Introductionmentioning
confidence: 99%